Association of maternal prepregnancy BMI with metabolomic profile across gestation - Hellmuth, C; Lindsay, K L; Uhl, O; Buss, C; Wadhwa, P D; Koletzko, B; Entringer, S (International Journal of Obesity, 2017)
Background/Objectives: Elevated prepregnancy body mass index (pBMI) and excess gestational weight gain (GWG) constitute important prenatal exposures that may program adiposity and disease risk in offspring. The objective of this study is to investigate the influence of pBMI and GWG on the maternal metabolomic profile across pregnancy, and to identify associations with birth weight. Subjects/Methods: This is a longitudinal prospective study of 167 nondiabetic women carrying a singleton pregnancy. Women were recruited between March 2011 and December 2013 from antenatal clinics affiliated to the University of California, Irvine, Medical Center. Seven women were excluded from analyses because of a diagnosis of diabetes during pregnancy. A total of 254 plasma metabolites known to be related to obesity in nonpregnant populations were analyzed in each trimester using targeted metabolomics. The effects of pBMI and GWG on metabolites were tested through linear regression and principle component analysis, adjusting for maternal sociodemographic factors, diet, and insulin resistance. A Bonferroni correction was applied for multiple comparison testing. Results: pBMI was significantly associated with 40 metabolites. Nonesterified fatty acids (NEFA) showed a strong positive association with pBMI, with specificity for mono-unsaturated and omega-6 NEFA. Among phospholipids, sphingomyelins with two double bonds and phosphatidylcholines containing 20:3 fatty acid chain, indicative of omega-6 NEFA, were positively associated with pBMI. Few associations between GWG, quality and quantity of the diet, insulin resistance and the maternal metabolome throughout gestation were detected. NEFA levels in the first and, to a lesser degree, in the second trimester were positively associated with birth weight percentiles. Conclusions: Preconception obesity appears to have a stronger influence on the maternal metabolic milieu than gestational factors such as weight gain, dietary intake and insulin resistance, highlighting the critical importance of preconception health. NEFA in general, as well as monounsaturated and omega-6 fatty acid species in particular, represent key metabolites for a potential mechanism of intergenerational transfer of obesity risk.